Perancangan User Interface/User Experience Aplikasi Mobile Menggunakan Metode Design Thinking Pada Only One Cloth Di Purwakarta - Budiharto, Sigit; Ramadhan, Yudhi Raymond; T, Moch. Hafid (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The most important stage in making a mobile application is designing an attractive display design. The Only One Cloth store still uses social media to sell products, besides that the factors that are still limited to the Only One Cloth Store are the lack of payment system organization and descriptions, therefore an application display that is needed by the store and potential users is made. The user interface (UI) is a form of graphical display that relates to potential users. User Interface works to connect users with the operating system on the computer so that prospective users can use it easily. Making the application display uses the iterative Design Thinking method where we try to understand the user, challenge assumptions, and redefine the problem in an effort to find alternative strategies and solutions. The Design Thinking method consists of five stages, namely Emphatize, Define, Ideate, Prototype, Test. At the Test stage, a test will be carried out on the value given to the task from the application display that has been made. The values that have been collected will be tested using the Single Ease Question (SEQ) method and get a value of 6.4 from the total tasks that have been assessed, if one task has a value of 5.5 then it must be iterated again. Judging from the SEQ results from the appearance of the application that is made feasible 6.4 then the appearance of the application is already easy to use by potential users